Increased cardiovascular risk in epilepsy - Gaertner, Mark L.; Mintzer, Scott; DeGiorgio, Christopher M. (Frontiers in Neurology, 2024)
Epilepsy is known to be associated with increased risk of mortality and it is evident that a significant portion of this risk is conferred by cardiovascular risk factors. Recently there has been renewed interest in this association considering increased overall cardiac mortality in epilepsy that is distinct from the well-established concept of sudden unexplained death in epilepsy (SUDEP) which is proposed to result from a convulsive seizure event that may lead to respiratory compromise followed by hypoxia and results in cardiac arrest. Cardiac arrest due to causes not attributable to SUDEP, meaning not associated with a convulsive seizure, has been increasing and there is a renewed interest in the burden of cardiovascular risk factors. This review discusses the most common cardiovascular risk factors and their association with epilepsy including obesity, diabetes mellitus, and hyperlipidemia. Hyperlipidemia related to the use of enzyme inducing antiseizure medications is also discussed as a topic that is of particular importance to prescribers that have patients with comorbid cardiovascular risk and epilepsy. Heart rate variability (HRV) and its association with SUDEP is discussed as well as a contributor to vascular risk. Finally, the authors discuss a potential role for neurologists who treat epilepsy to engage closer with their patient's cardiovascular risk factors using available tools such as a the ASCVD score calculator to determine the overall risk of mortality, as well as acting upon this information to guide treatment approaches integrating the information provided in this review.